Systematic Review and Meta-Analysis of the Efficacy and Safety of Enhanced Recovery After Surgery vs. Conventional Recovery After Surgery on Perioperative Outcomes of Radical Cystectomy - Zhang, Dongxu; Sun, Kai; Wang, Tianqi; Wu, Gang; Wang, Jipeng; Cui, Yuanshan; Wu, Jitao (Frontiers in Oncology, 2020)
Radical cystectomy was characterized as the most difficult operation in urology field because of complex surgical procedures and postoperative complications. Enhanced recovery after surgery (ERAS) was widely used in clinical surgery which reduced the incidence of perioperative complications. Thus, we performed a meta-analysis to evaluate the efficacy and safety of (ERAS) versus conventional recovery after surgery (CRAS) on perioperative outcomes of radical cystectomy. Randomized controlled trials (RCTs), which involved a comparison of ERAS and CRAS, were searched by MEDLINE, EMBASE, and the Cochrane Controlled Trials Register. The reference lists of retrieved studies were also surveyed. Among seven RCTs involving 813 patients included in our meta-analysis, we find that the ERAS group had better performance in the following parameters: length of hospital stay (the mean difference [MD]= -1.12, 95%CI: -1.80 to -0.45, P=0.001), time to first flatus (MD = -0.70, 95%CI: -0.98 to 0.41, P<0.00001), and time to regular diet (MD = -0.12, 95%CI: -1.76 to -0.28, P=0.007). However, there were no significant differences between these two groups in major complications (odds ratio [OR]= 0.63, 95%CI= 0.63 to 1.34, P= 0.64), readmission (OR= 1.15, 95%CI= 0.65 to 2.01, P= 0.63), ileus (OR= 0.75, 95%CI= 0.44 to 1.28, P= 0.29), wound infection (OR= 0.56, 95%CI= 0.31 to 1.01,P= 0.05) or mortality (OR= 0.69, 95%CI= 0.24 to 1.99, P= 0.49). Moreover, the time to first bowel movement (MD= -0.55, 95%CI= -1.62 to 0.53, P= 0.32) did not show a significant difference between the two groups. ERAS reduced the length of hospital stay, time to first flatus and time to regular diet after cystectomy. Compared to CRAS protocol, ERAS protocol does not increase the risk of adverse events.